2016
DOI: 10.1038/srep32121
|View full text |Cite
|
Sign up to set email alerts
|

The antifungal plant defensin AtPDF2.3 from Arabidopsis thaliana blocks potassium channels

Abstract: Scorpion toxins that block potassium channels and antimicrobial plant defensins share a common structural CSαβ-motif. These toxins contain a toxin signature (K-C4-X-N) in their amino acid sequence, and based on in silico analysis of 18 plant defensin sequences, we noted the presence of a toxin signature (K-C5-R-G) in the amino acid sequence of the Arabidopsis thaliana defensin AtPDF2.3. We found that recombinant (r)AtPDF2.3 blocks Kv1.2 and Kv1.6 potassium channels, akin to the interaction between scorpion tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 59 publications
(89 reference statements)
1
25
0
Order By: Relevance
“…Here, we found Bldesin, a pathogenic fungus‐derived antimicrobial defensin peptide with Kv1.3 channel inhibitory activity. These results from our group and Cammue et al indicated that the interaction between natural defensin peptides from different organisms and human potassium channels might be common, which suggested that natural defensins from different organisms might be an important source for the lead drug discovery targeting human potassium channels …”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Here, we found Bldesin, a pathogenic fungus‐derived antimicrobial defensin peptide with Kv1.3 channel inhibitory activity. These results from our group and Cammue et al indicated that the interaction between natural defensin peptides from different organisms and human potassium channels might be common, which suggested that natural defensins from different organisms might be an important source for the lead drug discovery targeting human potassium channels …”
Section: Discussionsupporting
confidence: 64%
“…Then we reported the potassium channel‐blocking Plectasin, the first defensin blocker from the fungus kingdom . When we are researching whether there are other potassium channel defensin blockers from different organisms, Cammue et al from Belgium reported the first antifungal plant defensin AtPDF2.3 that blocks Kv1.2 and Kv1.6 potassium channels. Then, we found scorpion‐derived defensin peptide BmKDfsin4 could effectively inhibit Kv1.1, Kv1.2, and Kv1.3 channel currents .…”
Section: Discussionmentioning
confidence: 99%
“…In support of these concepts, Zhu et al reported that mutations of two residues in a core consensus insect defensin sequence possessing a structural signature related to toxogenic effects of scorpion venoms could convert a defensin into a neurotoxin [ 172 ]. Similarly, Vriens et al reported on the mutation of one residue in the sequence of the antifungal plant defensin PDF2.3 from Arabidopsis thaliana (AtPDF2.3), thereby converting its partial scorpion toxin signature into the full toxin signature [ 171 173 ]. As a consequence, this mutant AtPDF2.3 was characterized by antifungal activity and inhibitory activity toward mammalian Kv1.2 and Kv1.6 potassium channels [ 173 ].…”
Section: Development Of Peptide Anti-infectives Targeting Fungal Rmentioning
confidence: 99%
“…The Arabidopsis defensin type 2 family (PDF2s) has six members (Thomma et al, 2002). Electrophysiological studies have shown that AtPDF2.3 has potassium channel blocking activity (Kim et al, 2016). AtPDF2.5 is a Cd-induced protein that is located in cell walls of the vascular bundles in the xylem; it positively regulates Cd tolerance and accumulation by mediating the chelation and efflux of cytoplasmic Cd to the apoplast cell wall in Arabidopsis thaliana (Luo et al, 2019b).…”
Section: Introductionmentioning
confidence: 99%